Direct sonic and ultrasonic wave velocity in masonry under compressive stress - Manning, Elizabeth Campbell (2014)
Sonic Pulse Velocity Testing and Ultrasonic Testing are widely accepted non-destructive testing techniques that can be used to investigate historical masonry structures. Sonic pulse velocity tests have been used with various set-up configurations to investigate the interior consistency of masonry walls and columns and to assess the effectiveness of grout injection; and ultrasonic tests have been used on masonry materials to estimate their elasticity. The velocity at which a wave passes through the masonry can be influenced by many variables such as the mechanical characteristics of the materials, arrangement of constituents, joints and voids. Due to the irregularity of historical masonry and the large number of variables that can influence the wave velocity, only qualitative results from these tests can be obtained. This paper presents the results of a laboratory test plan aimed at investigating the relationship between wave velocity and the variable of masonry compressive stress. Ultrasonic tests were performed on the constituent materials, granite and mortar blocks, while they were loaded in compression. Then direct sonic tests were performed on small masonry wallets constructed of the same materials while they were loaded in compression. Test results of the masonry are discussed in relation to those of the constituent materials.